Are Agricultural Commodity Prices on a Conventional Wisdom with Inflation?. (August 2021) - Sun, Ting-Ting; Su, Chi-Wei; Tao, Ran; Qin, Meng
The study investigates the mutual influence between agricultural commodity prices (ACP) and inflation (INF) in China by employing the bootstrap full- and sub-sample rolling-window Granger causality tests. We find that ACP has positive effects on INF, indicating that agricultural commodities play a significant role in stabilizing general price levels, but the higher ACP may create inflationary pressures. However, the negative effects suggest that under the shock of external uncertainty, the rise of ACP is not always regarded as the prime driver of INF. The results are not consistent with Hypothesis 1, which highlights that INF is positively affected by ACP. In turn, we also find positive and negative impacts of INF on ACP, showing that the level of INF can affect the supply and demand of agricultural commodity markets, it can be considered as a factor affecting ACP. The findings support Hypothesis 2 derived from the interaction mechanism. These analyses can assist the Chinese government to understand that ACP is not an effective indicator for forecasting INF. It also can prompt them to pay attention to the transmission effect of price levels on ACP, to maintain the stability of the agricultural commodity market.